2015
DOI: 10.1186/s12913-015-1070-2
|View full text |Cite
|
Sign up to set email alerts
|

Perception of quality of care of patients with potentially severe diseases evaluated at a distinct quick diagnostic delivery model: a cross-sectional study

Abstract: BackgroundAlthough hospital-based outpatient quick diagnosis units (QDU) are an increasingly recognized cost-effective alternative to hospitalization for the diagnosis of potentially serious diseases, patient perception of their quality of care has not been evaluated well enough. This cross-sectional study analyzed the perceived quality of care of a QDU of a public third-level university hospital in Barcelona.MethodsOne hundred sixty-two consecutive patients aged ≥ 18 years attending the QDU over a 9-month per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
1
5
1
Order By: Relevance
“…The results showed that the factor associated with patients' satisfaction within the dimension of identity-oriented approach of the caregivers, including the quality of information, encouragement and participation, was self-estimated physical health. This contrasts with previous research [8][9][10] showing that the most important predictor of satisfaction across settings is age. Within the dimension of identity-oriented approach of the caregivers, which was the largest dimension, participants who estimated their physical health as being good were more satisfied than those who reported their physical health as being less than good.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results showed that the factor associated with patients' satisfaction within the dimension of identity-oriented approach of the caregivers, including the quality of information, encouragement and participation, was self-estimated physical health. This contrasts with previous research [8][9][10] showing that the most important predictor of satisfaction across settings is age. Within the dimension of identity-oriented approach of the caregivers, which was the largest dimension, participants who estimated their physical health as being good were more satisfied than those who reported their physical health as being less than good.…”
Section: Discussioncontrasting
confidence: 99%
“…Within the dimension of identity-oriented approach of the caregivers, which was the largest dimension, participants who estimated their physical health as being good were more satisfied than those who reported their physical health as being less than good. Such results are consistent with the findings of previous studies 6,7,9 conducted in other care settings, which were that good health correlates with perceptions of good care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition to a time to diagnosis similar to the length-of-stay for similar conditions, QDUs are useful to decrease referrals from PC to emergency departments (EDs), are cost-saving, and are associated with higher patients’ satisfaction scores than hospitalization. [ 12 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…Although reported data on these units are limited, several advantages over hospitalization have been established: in addition to ensuring a time to diagnosis similar to the length of stay for the same evaluable conditions, they are known to decrease emergency department (ED) referrals from PC easing ED overcrowding, are associated with higher patient satisfaction scores, and are considerably cost-saving [ 11 13 , 15 , 16 , 25 29 ]. Yet to be evaluated, patients’ physical performance should allow them to travel from home to hospital and back for visits and investigations.…”
Section: Introductionmentioning
confidence: 99%